Safety assessment of a new matrix metalloproteinase inhibitor extracted from Lupinus albus seeds, through the analysis of its cytotoxic and genotoxic properties - Bischoff, Nicolaij (2020)
Colorectal cancer (CRC) is the third most common cancer worldwide, being highly metastatic and mostly resistant to anticancer treatment. Especially due to its high incidence in young people and the lack of adequate treatment, CRC is an increasing health risk for future generations. Since death of most colon cancer patients is due to metastatic disease, rather than the primary tumors itself, the mechanisms in the metastatic progression of CRC are intensively being studied. Subgroups of matrix metalloproteinase´s (MMP´s), especially gelatinases (MMP-2, MMP-9) have been identified to be frequently involved in the metastatic process, which makes them a useful drug target. On the other hand, experimental, epidemiological and clinical studies have shown that the consumption of legumes significantly reduces the incidence of several tumor types, including CRC. These effects are generally associated with the inhibitory action of legume seeds on MMP’s. MMP play a key role in cellular homeostasis due to their ability to initiate, enhance or down-regulate signal cascades, involving cell growth, inflammation, cytokine and growth-factor release. Overexpression of MMPs results in matrix degradation and is strongly associated with cancer cell invasion and metastasis. Deflamin is a novel matrix metalloproteinase inhibitor (MMPI) extracted from the seeds of Lupinus albus, which exhibits anti-inflammatory properties, particular at the gastrointestinal level and has been pointed as a promising cancer preventive agent. It shows especially high inhibitory activity against MMP-2 and MMP-9. This makes deflamin a great candidate to become a valuable anti-inflammatory nutraceutical agent, as well as a useful asset in the treatment of inflammatory bowel diseases (IBD). However potential secondary adverse effects must be avoided and for that purpose an early evaluation of its potential toxic effects to human cells is needed. This work is aimed at contributing to the safety evaluation of deflamin through the analysis of cytotoxic and genotoxic properties of the purified deflamin and a Lupinus albus extract in Caco-2 cells. Furthermore, its bioavailability and transport via a Caco-2 monolayer system will be tested to get further insights on possible uptake scenarios in the human intestine. The cytotoxic effects are analyzed by assessing cell viability (MTT assay), following Caco-2 cells exposure to a concentration range (5-640 µg/ml) of the pure deflamin or the extract during 24, 48 and 72 hours. Genotoxicity is assessed by the alkaline comet assay and the cytokinesis-block micronucleus assay. The effects on the intestinal barrier are analyzed by measuring the transepithelial resistance (TER) in a differentiated Caco-2 monolayer upon apical exposure to deflamin or the extract. Preliminary data suggests that neither the pure deflamin nor the extract display cytotoxicity in the tested concentration range. The results of the genotoxicity studies will be presented and discussed, in the light of the future application of deflamin as a chemopreventive agent, ensuring the absence of adverse side effects.